Sri Lanka Education Sector Assessment : Achievements, Challenges, and Policy Options - Dundar, Halil; Millot, Benoit; Riboud, Michelle; Shojo, Mari; Aturupane, Harsha; Goyal, Sangeeta; Raju, Dhushyanth (Washington, DC: World Bank, 2017)
A country’s education system plays a pivotal role in promoting economic growth and shared prosperity. Sri Lanka has enjoyed high school-attainment and enrollment rates for several decades. However, it still faces major challenges in the education sector, and these challenges undermine the country’s inclusivegrowth goal and its ambition to become a competitive upper-middle-income country. The authors of Sri Lanka Education Sector Assessment: Achievements, Challenges, and Policy Options offer a thorough review of Sri Lanka’s education sector—from early childhood education through higher education. With this book, they attempt to answer three questions: • How is Sri Lanka’s education system performing, especially with respect to participation rates, learning outcomes, and labor market outcomes? • How can the country address the challenges at each stage of the education process, taking into account both country and international experience and also best practices? • Which policy actions should Sri Lanka make a priority for the short and medium term? The authors identify the most critical constraints on performance and present strategic priorities and policy options to address them. To attain inclusive growth and become globally competitive, Sri Lanka needs to embark on integrated reforms across all levels of education. These reforms must address both short-term skill shortages and long-term productivity. As Sri Lanka moves up the development ladder, the priorities of primary, secondary, and postsecondary education must be aligned to meet the increasingly complex education and skill requirements.